THU0108 REAL-WORLD RADIOGRAPHIC PROGRESSION IN RA WITH BIOLOGIC DMARDS. (2nd June 2020) - Pamplona Bueno de Andrade, N.; Palominos, P.; Hax, V.; Gasparin, A. A.; Cé Bressan, V.; Guimarães Da Silveira, L.; Brenol, C.
Abstract : Background: As structural damage is irreversible and strongly associated with functional disability 1, it is an important outcome to be prevented in rheumatoid arthritis (RA). Acute phase markers, rheumatoid factor (RF) and anti-citrullinated protein (anti-CCP) positivity are important predictors of erosive disease 2 . Previous studies conducted in real life setting have divergent results regarding the role of disease activity in radiographic progression 3, 4 . Objectives: To evaluate the impact of disease activity and biologic disease modifying anti-rheumatic drugs (bDMARDs) on radiographic progression of established RA in clinical practice in southern Brazilian public health system. Methods: Longitudinal retrospective study including patients with RA (1987 ACR criteria) treated with bDMARDs and followed from 2015 to 2019. Clinical and demographic data were collected at baseline. Radiographs of hands and feet were performed yearly. X-rays were scored according to the van der Heijde-modified total Sharp method (vdH-mTSS) in known chronological order. Clinical relevant radiographic progression (CRRP) was defined as an increase ≥3 units on the score per year5.Demographic, clinical, and radiographic characteristics of RA patients with or without relevant progression were compared with Fisher exact and Mann-Whitney test. Results: Seventy-five patients were included. The patients' characteristics are shown in table 1 . Twenty three (30%) patients presented CRRP at any time point of the follow up (figure 1 ). Mean DAS28-ESR at baseline was higher in patients who progressed radiographically, than those who did not progress (4.8±1.1 vs 3.5±1.1; p < 0.001). No patient in remission at baseline presented with CRRP. Radiographic progression occurred in 15% of patients in low disease activity, 34% of patients in moderate disease activity and 57% of patients in high disease activity at baseline, depicting a linear relation between categories of disease activity and CRRP. RF, anti-CCP, disease duration, educational level, smoking status, total vdH-mTSS at baseline, number and duration of biologic DMARDs were not associated with CRRP. No single biologic DMARD was associated with worse radiological prognosis. Conclusion: In contrast to controlled clinical trials, real-world studies have shown that patients with RA treated with bDMARD still develop radiological progression. We observed that despite prognostic factors, achievement of treatment target is the most important factor to prevent articular damage in RA. References: [1]Ann Rheum Dis 2012;71(6):836-44 [2]Rheumatology 2016;55:1053-1065 [3]Arthritis Res Ther 2019;21(1):237 [4]Medicine 2016;95(17) [5]Ann Rheum Dis 2005; 64(2): 179–182 Disclosure of Interests: Nicole Pamplona Bueno de Andrade: None declared, Penelope Palominos Grant/research support from: This work was sponsored by the regional society of rheumatology (Sociedade de Reumatologia do Rio Grande do Sul)., Vanessa Hax: None declared, Andrese Aline Gasparin: None declared, Vanessa Cé Bressan: None declared, Letícia Guimarães da Silveira: None declared, Claiton Brenol: None declared